Activation of Extracellular Signal-Regulated Kinase 2 and cAMP Response Element-Binding Protein in Cultured Neurons by the Macrocyclic Ellagitannin Oenothein B - Satoshi Okuyama; Morio Yoshimura; Yoshiaki Amakura; Mitsunari Nakajima; Yoshiko Furukawa (NeuroSci, 2022)
(1) Background: The findings of our recent in vivo study indicated that the oral administration of oenothein B, a unique macrocyclic ellagitannin, activated extracellular signal-regulated kinase (ERK) 2 and cAMP response element-binding protein (CREB) in the mouse brain. A large hydrophilic oenothein B is unable to reach the brain, suggesting that any metabolite(s) of oenothein B might function in the brain. (2) Results: The addition of oenothein B to the culture medium of rat cortical neurons induced the prompt and significant activation of ERK2 and CREB. (3) Conclusions: The activation of ERK2 and CREB is crucial for synaptic transmission and learning/memory formation in the brain. The present results suggest oenothein B exerts neurotrophic/neuroprotective effects in the brain through the modulation of neuronal signaling pathways, if it reaches the brain.